A methodology for quantifying and characterizing litter from trash capture devices (TCDs) to measure impact and inform upstream solutions - Cassandra Sherlock; Rafaela F. Gutierrez; Michael David; Chelsea M. Rochman (Canadian Science Publishing, 2023)
Trash capture devices (TCDs) are a rapidly evolving tool for municipal governments, non-governmental organizations, and industries to divert litter from our waterways. Here, we introduce protocols to initiate trash trapping projects to quantify and characterize captured anthropogenic litter based on a case study using Seabins. In addition, we have introduced a network for global data collection via TCDs. Our first protocol is a visual audit of the potential site to inform the type and location for TCD deployment. Our next two protocols quantify and characterize the litter captured by TCDs: (1) a simple protocol intended for daily monitoring and (2) a detailed protocol to characterize and quantify all large debris (>3 cm) and a subset of the small debris (2 mm-3 cm) caught in the devices. Using Seabins in the Toronto Harbour to test our methodology, we found that our subsampling methodology has a 6.9% error rate. Over a 19-week period, the Seabins captured ∼85 000 pieces of small debris. Our study highlights the utility of TCDs and proposes methods to realize this utility globally. TCDs should become more widespread and utilized as a triple threat: a cleanup tool, a data collection tool, and a platform for outreach and education.